2009
DOI: 10.1007/978-1-59745-416-2_17
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Gene Expression in Esophageal Cancer

Abstract: Esophageal cancer is a significant worldwide health problem because of its poor prognosis and high incidence in certain parts of the world. Tobacco smoke and alcohol consumption are significant risk factors for esophageal squamous cell carcinoma, whereas frequent gastroesophageal reflux and subsequent inflammatory reactions play a role in causing the adenocarcinoma. Esophageal carcinogenesis involves multiple genetic alterations. A large body of knowledge has been generated regarding molecular alterations asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 117 publications
1
41
0
Order By: Relevance
“…Therefore, aberrant methyl transfer caused by the inhibition of SAM synthesis may be important for alcohol-mediated carcinogenesis [3]. Retinoic acid (RA) regulates the transcription of many genes that are important for cellular growth and differentiation by signaling through its nuclear receptors (RARs) [7]. Chronic alcohol consumption decreases RA concentrations in the liver by inducing CYP2E1 [33].…”
Section: Well-established Carcinogens In Alcohol and Its Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, aberrant methyl transfer caused by the inhibition of SAM synthesis may be important for alcohol-mediated carcinogenesis [3]. Retinoic acid (RA) regulates the transcription of many genes that are important for cellular growth and differentiation by signaling through its nuclear receptors (RARs) [7]. Chronic alcohol consumption decreases RA concentrations in the liver by inducing CYP2E1 [33].…”
Section: Well-established Carcinogens In Alcohol and Its Metabolitesmentioning
confidence: 99%
“…Cigarette smoking and alcohol consumption are considered to be significant risk factors for esophageal squamous cell carcinoma (ESCC) [7][8][9]. Various kinds of genetic abnormalities have been investigated in ESCC, including the activation of oncogenes and inactivation of tumor-suppressor genes, and a large body of knowledge has been obtained concerning esophageal carcinogenesis [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…More than 80% of EC cases in China are squamous cell carcinoma, but the majority in the West are adenocarcinoma (Lambert et al, 2007). The risk factors for EC in Chaoshan are smoking, alcohol consumption, and drinking or eating at high temperatures (Xu et al, 2009;Lin et al, 2011). The risk factors for EC in the West are gastroesophageal reflux disease and Barrett's esophagus (Rastogi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to nAchR, nicotine could also bind to EGFR and AR-β and acts as a growth factor. Epidermal growth factor receptor (EGFR) is a tyrosine kinase receptor and plays an important role in growth, development, and tumorgenesis (40). NNK contributes to cancer cell proliferation not only by synthesis of thromboxane A2 (TXA2), but also by activating TXA2 receptor, as well.…”
Section: Tobacco and Growth Signaling Pathwaysmentioning
confidence: 99%
“…It seems that cyclooxygenase-2 (COX-2) elevates both angiogenesis and aggressive potential of tumor cells by increasing the production of prostaglandins and converting the pre-cancerous agents to carcinogens. It is demonstrated that nicotine increases metastasis of esophageal carcinoma by up-regulating and enhancing the activity of both MMP-2 and COX-2 (40). In another study, it is shown that nicotine plays an important role in migration of tumor cells mostly via increasing the expression of several chemokines/chemokine receptors, such as CXCR2, CXCR3, CXCR4 and CCL12 (50).…”
Section: The Impact Of Tobacco On Angiogenesis and Cancer Metastasismentioning
confidence: 99%